Modelling material failure on large deformation processes - J. M. A. César de Sá (2007)
A non-local damage model for material failure at large deformations is presented. The model is tested in different numerical frameworks, i.e., the Finite Element Method and a meshfree method, the Reproducing Kernel Particle Method, and for different forming processes like forging or sheet forming.